Subirrigated Caladium Tuber Production and Water Use as Affected by Water Table Level - Craig D. Stanley; Brent K. Harbaugh (EDIS)
This is document SL 208, a publication of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published October 2003.